Religions - a Janus-Faced Phenomenon in Local Politics. Issue 2 (6th November 2020) - Axelson, Tomas; Stier, Jonas
Abstract : Religions can facilitate cohesion,   belonging and feelings of safety or can underpin tensions, separatism or terrorism. This has led local, national and international policymakers to use inter-religious councils to overcome local conflicts by facilitating dialogue. Sweden has a growing number of inter-religious councils around the country. This article focuses on the inter-religious council in Midtown. The aim is (1) to describe how politicians, civil servants and religious leaders as participants in the council express their expectations on the Midtown  inter-religious council, and (2) to analyse these accounts in the light of ongoing research and European examples of inter-religious dialogue. Data have been collected via interviews and participant observation, and analysed through two critical lenses, one focusing on social cohesion, the other on fears of militant religious extremism. Results show that members of the Midtown council view religions as constituting possible obstacles but mainly as an important  asset in a process of developing a cohesive society.